Evaluation of serum concentrations of cortisol and thyroxine in bitches with early-stage mammary carcinoma - Salomão, Ricardo L. (2018)
In view of the fact that cancer is considered a chronic disease that can interfere with hormonal homeostasis by means of cytokines, we hypothesized that, even at early stages, mammary carcinoma is able to alter the balance of the hypothalamic-pituitary-thyroid and hypothalamic-pituitary-adrenal axes. To test this hypothesis, the serum concentrations of basal cortisol, thyroxine (T4), free thyroxine (fT4), and thyroid-stimulating hormone (TSH) were evaluated in 20 unspayed bitches that had a histopathological diagnosis of grade 1 mammary carcinoma at clinical stage I according to the World Health Organization (WHO) classification (T1N0M0). The control animals comprised 10 unspayed bitches in perfect health conditions that were matched with those with mammary carcinoma by age. No significant differences regarding the concentrations of basal cortisol, TSH, t4, and fT4 were found between the bitches carrying early stage mammary carcinoma when compared to the control group. This suggests that, even if malignant, early-stage mammary carcinomas do not exhibit the ability to alter the concentrations of hormones produced by the hypothalamic-pituitary-adrenal or hypothalamic-pituitary-thyroid axes.